2020
DOI: 10.1108/sasbe-05-2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of ocean-based renewable energy for West Africa’s sustainable energy future

Abstract: PurposeThe limited supply of fossil fuels, constant rise in the demand of energy and the importance of reducing greenhouse emissions have brought the adoption of renewable energy sources for generation of electrical power. One of these sources that has the potential to supply the world’s energy needs is the ocean. Currently, ocean in West African region is mostly utilized for the extraction of oil and gas from the continental shelf. However, this resource is depleting, and the adaptation of ocean energy could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Solar energy development in Nigeria is faced with a lack of enabling vision and mission for technology, fine-tuning and promoting the initiative (Haas et al , 2018). Although, the country has opportunities for solar radiation potentials, the market is still immature, and the turnout for utilisation is low (Abdullahi et al , 2017a; Adesanya et al , 2020). The Power Sector Reform Act.…”
Section: Barriers For Solar Energy Implementation In Nigeriamentioning
confidence: 99%
“…Solar energy development in Nigeria is faced with a lack of enabling vision and mission for technology, fine-tuning and promoting the initiative (Haas et al , 2018). Although, the country has opportunities for solar radiation potentials, the market is still immature, and the turnout for utilisation is low (Abdullahi et al , 2017a; Adesanya et al , 2020). The Power Sector Reform Act.…”
Section: Barriers For Solar Energy Implementation In Nigeriamentioning
confidence: 99%
“…Moreover, the authors in [19] have investigated how to achieve sustainable development by studying the impact of generating renewable energy on the economy and the environment. Similarly, they studied the use of ocean-based renewable energy for generating electrical power and analyzed the economic and environmental impacts of adopting their approach [20]. Their results have shown that the proposed approach is capable to generate the required energy in order to supply the energy demands.…”
Section: Introductionmentioning
confidence: 99%
“…Cities' air quality in some countries is gradually declining (Adesanya et al , 2021; Asante et al , 2016; Dash, 2021; Dobbelsteen et al , 2020; Kwong et al , 2021; Rahmouni and Smail, 2020). It is often seen that developing countries suffer from air pollution more than developed ones (Dash, 2021; Han and Keeffe, 2020; Liaros, 2020; Nguyen and Dang, 2020; Palencia et al , 2021; Rosenbaum et al , 2015; Smits, 2020; Taleb and Abumoeilak, 2021).…”
Section: Introductionmentioning
confidence: 99%